A Legal Analysis of Law Number 11 of 2012 on the Juvenile Criminal Justice System within Indonesian Criminal Law - Ayurisna, Maura Afda (The Future of Education Journal, 2025)
This study analyzes Law Number 11 of 2012 concerning the Juvenile Criminal Justice System within the framework of Indonesian criminal law. The research aims to examine the substance of the law, identify weaknesses in the regulation of criminal sanctions for children, and propose recommendations for future legal reform. This study employs a normative juridical method with a descriptive-analytical approach by analyzing legal norms, statutory provisions, and scholarly doctrines relevant to juvenile criminal justice. The research utilizes secondary data, including primary legal materials such as the Criminal Code (KUHP), Law Number 35 of 2014 on Child Protection, and Law Number 11 of 2012 on the Juvenile Criminal Justice System, as well as supporting secondary and tertiary legal materials. The findings indicate that the law embodies the principles of restorative justice and ultimum remedium as the foundation of child protection in criminal proceedings. However, its implementation still faces several challenges, particularly the inconsistency between Law Number 11 of 2012 and Supreme Court Regulation Number 4 of 2014 regarding the application of diversion. In addition, the restriction that prevents imprisonment for children under 12 years old creates a legal gap in dealing with serious offenses committed by minors, leading to public concern over justice and deterrence. Therefore, legal reform is required to strengthen the consistency of restorative justice practices, enhance the competence of law enforcement officers, and ensure that juvenile criminal sanctions remain educational, rehabilitative, and aligned with the best interests of the child.